2015
DOI: 10.1007/s12022-015-9405-4
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-Induced Senescence in Pituitary Adenomas—an Immunohistochemical Study

Abstract: Oncogene-induced senescence (OIS) serves as an initial barrier to cancer development, being proposed as a possible explanation for the usually benign behavior of the pituitary adenomas. We aimed to explore the immunohistochemical expression of the OIS markers, senescence-associated lysosomal β-galactosidase (SA-β-GAL), p16, and p21 in different types of 345 pituitary adenomas and compared it with the expression in the normal pituitary and in the specimens from the repeated surgeries. SA-β-GAL was overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
1
13
1
5
Order By: Relevance
“…Intriguingly, these reports are consistent with our finding and these pathways should be further investigated for their potential therapeutic value. Meanwhile, our results, together with those of previous studies, suggested that other processes such as oncogene-induced senescence attenuate the changes in the downstream of PI3K/Akt/mTOR pathway in these benign tumors [34, 35]. …”
Section: Discussionsupporting
confidence: 84%
“…Intriguingly, these reports are consistent with our finding and these pathways should be further investigated for their potential therapeutic value. Meanwhile, our results, together with those of previous studies, suggested that other processes such as oncogene-induced senescence attenuate the changes in the downstream of PI3K/Akt/mTOR pathway in these benign tumors [34, 35]. …”
Section: Discussionsupporting
confidence: 84%
“…OIS has been proposed as a possible explanation for the prevalently benign behaviour of pituitary adenomas. However, in this patient, a very low prevalence of p16 and p21 positive nuclei, did not support senescence as the explanation for tumour 's low proliferative activity, although it was in consonance with the hormonal activity [22,23]. Importantly, studies that compare the biology of pituitary adenomas and their radiological properties using magnetic resonance and PET/CT are still lacking.…”
Section: Opis Przypadkucontrasting
confidence: 63%
“…Indeed, the characterization of pituitary adenomas on the basis of genetic and molecular characteristics, and the link between these markers and clinical behavior, has grown exponentially within the past decade. 3,8,11,18 Given the recent advances in our knowledge in these fields, biopsy specimen preservation and biobanking for research studies are arguably more important now than at any time in the past.…”
Section: Discussionmentioning
confidence: 99%